Implication of Agriculture and Rural Economy nexus in Rural Planning: A Case Study of Nimpara Union, Charghat, Rajshahi - Zinia, Faria Afrin; Anam, Md Sadrul; Hossain, A K M Sadat (Journal of Bangladesh Institute of Planners, 2015)
Bangladesh is predominantly an agricultural country and this sector plays a pivotal role in accelerating the economic growth. But this sector is beset with many problems which causes low rate of return, seasonal unemployment etc. Because of low economic return, many farmers and agricultural labors have bound to shift in other occupations and/or migrate to another region. This paper is an initiative to find out whether agriculture is supporting rural economy satisfactorily or not. The research is based on primary and secondary data. Participatory Rural Appraisal (PRA) has been used as a tool in primary data collection. The primary data suggests that there is seasonal unemployment in agriculture sector that induces migration. The secondary data analysis has concluded that owing to lower wage and economic benefit, human involvement is being reduced in this sector day by day. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 233-241